Perceptions of Physical Education undergraduate on school inclusion: reconstructions by intervention in initial training - Camila Lopes de Carvalho; Marina Brasiliano Salerno; Mariana Piculli; Paulo Ferreira de Araújo (Motrivivência, 2017)
http://dx.doi.org/10.5007/2175-8042.2017v29n50p153